Using the National Diabetes Audit to improve the care of diabetes in secure hospital in-patient settings in the UK. Issue 3 (4th May 2017) - Puzzo, Ignazio; Gable, David; Cohen, Alan
Abstract: To examine the ability of two forensic units, one high secure and one medium secure, to meet the NICE (National Institute for Health and Care Excellence) standards of care for diabetes. We applied the National Diabetes Audit programme, which uses as standards the NICE guidelines, to assess the quality of care provided for patients in two forensic units. Of the 500 patients, 200 in high secure and 300 in medium secure, 88 (17.6%) had type 2 diabetes. None had Type 1 diabetes. Of those with Type 2 diabetes, the care of 74 (84%) met all 8 NICE recommended standards. Glucose levels were lower in the medium/low secure unit compared to the higher security environment. Whilst achievement of process-based outcomes was higher than those reported nationally, achieving clinical outcomes was more challenging. High-quality diabetic care can be provided for patients in forensic units. Benchmarking physical health outcomes against national criteria in mental health inpatients is a potential method of improving outcomes.